Real world initiation of newly funded empagliflozin and dulaglutide under special authority for patients with type 2 diabetes in New Zealand - Lynne Chepulis; Mark Rodrigues; Han Gan; Rawiri Keenan; Tim Kenealy; Rinki Murphy; Leanne Te Karu; Jo Scott-Jones; Penny Clark; Allan Moffitt; Sara Mustafa; Ross Lawrenson; et al. (BMC Health Services Research)
Abstract Background Type 2 diabetes (T2D) is sub-optimally managed for many in Aotearoa New Zealand, and disproportionately affects Māori and Pacific peoples. In February 2021, SGLT2i/GLP1RA agents were funded for use for the first time with prioritisation for Māori, Pacific and those with cardiovascular and/or renal disease or risk (CVRD). This study evaluates the impact of health system factors on initiation of SGLT2i/GLP1RA therapy. Methods Primary care data was collected for patients with T2D aged 18–75 years from four primary care organisations (302 general practices) in the Auckland / Waikato region of New Zealand (Feb 2021 – July 2022). Initiation of SGLT2i/GLP1RA therapy was reviewed by patient (age, gender, ethnicity, CVRD status) and health system variables (funding, provider type, staffing, patient numbers, rurality, after-hours access). Logistic regression was used to estimate the odds ratio of a patient being dispensed SGLT2i/GLP1RA. Results Of 57,743 patients with T2D, 22,331 were eligible for funded SGLT2i/GLP1RA access and 10,272 of those (46.0%) were prescribed. Initiation of therapy was highest in Māori (50.8%) and Pacific (48.8%) patients (vs. 36·2–40·7% of other ethnic groups; P < 0.001), but was comparable in those with and without CVRD (47·1% vs. 48·9%; P = 0.2). Prescribing was highest in practices with higher doctor/patient numbers, low-cost fees, Māori health providers and clinics without after-hours access. Conclusion Prioritised access for SGLT2i/GLP1RA appears to be associated with a reduced health equity gap for Māori and Pacific patients with T2D in NZ, but work is required to improve prescribing for patients with CVRD.